Political institutions and political elites in changing liberal-democracies - Vercesi, Michelangelo (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2020)
Contemporary liberal-democracies are under stress and traditional political parties have become detached from their electorates. Since the 1980s, parties have been experiencing a crisis of legitimation, whose effects have become intensive especially in the early twenty-first century. New populist challengers have tried to fill the representative void left by mainstream parties; at the same time, technocracy has become one of the most prominent form of representation. Political responsibility and responsiveness appear often incompatible in the eyes of voters. Moreover, political personalization and processes of presidentialization have led to a situation where single political leaders have become the crucial political actors, to the detriment of party organizations. This Habilitation thesis investigates the linkage between representative democratic institutions in parliamentary and semi-presidential systems and political elites, trying to understand how this linkage has been affected by the change of party democracy. In particular, the thesis analyzes political institutions’ functioning in democratic contexts as well as parties’ responses and elites’ paths to power as indicators of a process of adaptation. Four main research questions inform the analysis: what structural opportunities and constraints do political elites meet when it comes to exercising political power?; how have the decline of party government and political personalization modified opportunity structures?; how do parties and elites cope with democratic change?; has democratic change produced new criteria for successful political careers? The institutional focus is on political executives and representative assemblies at different levels of government. Findings highlight that political elites adopts strategies of resistance and respond to democratic change through incremental steps. In other words, rather than anticipatory, political elites appear reactive, when they are confronted with substantial modifications of the political opportunity structure. Overall, the study contributes to the debate about the changing role of parties and political elites as connectors between the state and the society and provides insights about future developments.

Die liberalen Demokratien der Gegenwart stehen unter Stress und die traditionellen politischen Parteien haben sich von ihren Wählern losgelöst. Seit den 1980er Jahren befinden sich die Parteien in einer Legitimationskrise, deren Auswirkungen vor allem zu Beginn des einundzwanzigsten Jahrhunderts sichtbar geworden sind. Neue populistische Herausforderer haben versucht, die von den Mainstream-Parteien hinterlassene Repräsentationslücke zu füllen; gleichzeitig ist die Technokratie zu einer der prominentesten Repräsentationsformen geworden. Politische Verantwortung und Responsivität scheinen in den Augen der Wähler oft unvereinbar zu sein. Darüber hinaus haben politische Personalisierung und Präsidialisierungstendenzen zu einer Situation geführt, in der einzelne „Führungspersönlichkeiten“ zu den entscheidenden politischen Akteuren geworden sind, zum Nachteil der Parteiorganisationen. Diese Habilitationsschrift untersucht die Beziehung zwischen repräsentativen demokratischen Institutionen in parlamentarischen und semipräsidentiellen Systemen und politischen Eliten und versucht zu verstehen, wie diese Beziehung durch den Wandel der Parteiendemokratie beeinflusst wurde. Insbesondere analysiert diese Arbeit das Funktionieren politischer Institutionen in demokratischen Kontexten sowie die Reaktionen der Parteien und die Wege der Eliten zur Macht als Indikatoren für einen Anpassungsprozess. Die Analyse stützt sich auf vier zentrale Forschungsfragen: Welchen strukturellen Chancen und Zwänge sind politische Elite bei der Ausübung politischer Macht ausgesetzt?; wie haben der Niedergang des „Party Government“ und die politische Personalisierung Opportunitätsstrukturen verändert?; wie gehen Parteien und Eliten mit dem demokratischen Wandel um?; hat der demokratische Wandel neue Kriterien für erfolgreiche politische Karrieren hervorgebracht? Der institutionelle Schwerpunkt liegt auf politischen Exekutiven und repräsentativen Versammlungen auf verschiedenen Regierungsebenen. Die Ergebnisse zeigen, dass die politischen Eliten Strategien des Widerstands verfolgen und auf den demokratischen Wandel nur schrittweise reagieren. Mit anderen Worten: Politische Eliten erscheinen eher reaktiv als antizipierend, wenn sie mit substanziellen Veränderungen der politischen Gelegenheitsstruktur konfrontiert werden. Insgesamt leistet die Studie einen Beitrag zur Debatte über die sich wandelnde Rolle von Parteien und politischen Eliten als Bindeglied zwischen Staat und Gesellschaft und liefert Einschätzungen für zukünftige Entwicklungen.
Politische Institutionen und politische Eliten im Wandel der Liberaldemokratien
Keywords: 324 Der politische Prozess